Preparation method of high and low temperature bonding slurry and lithium battery diaphragm and lithium battery

By using high and low temperature bonding pulp, low -temperature adhesion materials are covered with high temperature adhesion materials, and appropriate thickening agents, binders and dispersers are added to solve the problem of poor lithium battery diaphragm and polar adhesion. A stable adhesion performance in high and low temperature environment is achieved to ensure stable battery safety and performance.

CN119340618AActive Publication Date: 2025-01-21HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411353129.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-21
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The adhesive strength between the water-based bonding materials for existing lithium batteries and the electrode sheet is poor, and it needs to be softened under high temperature environment to have better bonding.

Method used

High and low temperature bonding slurry is used, including low temperature bonding material coating high temperature bonding material, and the bonding material is obtained by mixing evenly, melting, extruding and granulating, and adding thickeners, binders and Dispersant to form adhesive slurry suitable for high and low temperature environments.

Benefits of technology

The height temperature adhesion of the lithium battery diaphragm and the polar sheet is improved to ensure that the battery has stable performance in the life cycle, and avoids the safety of battery packs, short, self -discharge, spontaneous combustion and explosion caused by insufficient adhesion. Hidden dangers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340618A_ABST
    Figure CN119340618A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a preparation method of high and low temperature adhesive slurry and a lithium battery diaphragm, and a lithium battery. The high and low temperature bonding slurry comprises the following components in parts by mass: 10-15 parts of a bonding material, 5-15 parts of a thickening agent, 2-15 parts of a binder, 0-0.5 part of a dispersing agent and 50-80 parts of water, the bonding material is a low-temperature bonding material coated high-temperature bonding material, and the bonding material comprises the low-temperature bonding material and the high-temperature bonding material in a mass ratio of 1: 9-9: 1. According to the technical scheme, the problems that the water-based adhesive material for the lithium battery in the prior art is poor in adhesive force with the pole piece and has relatively good adhesive property only after being softened in a high-temperature environment are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a high-low temperature bonding slurry and a lithium battery separator, and a lithium battery. Background Art

[0002] As the demand for battery energy density becomes higher and higher, the amount of emerging materials such as high nickel and silicon carbon is increasing. While these materials provide high capacity, they have significant cyclic shrinkage and expansion during the charge and discharge process, causing the electrode group system composed of electrode-diaphragm-electrode to twist and deform during creeping and even form gaps. At the very least, it affects the shape of the battery and causes the battery pack to swell. At worst, it causes lithium deposition on the surface of the negative electrode, causing safety hazards such as internal short circuit, self-discharge, spontaneous combustion, and explosion.

[0003] In order to solve the above problems, the commonly used method is to modify the surface of the diaphragm to make it adhesive, so that an adhesive layer is formed between the electrode-diaphragm-electrode system and the interface is solidified; commonly used adhesive materials include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP copolymer), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), etc.; the process routes used are oil-based (the polymer is dissolved in an organic solvent, the solution is coated, and the surface of the polyolefin-based membrane is modified) and water-based (the polymer is dispersed in water to form a suspension of the polymer, the suspension is coated, and the surface of the polyolefin-based membrane is modified).

[0004] The oil-based route has better bonding effect between the diaphragm and the electrode, but the cost of solvent and environmental control is high; the most commonly used PVDF-HFP copolymer in the water-based route uses water as the dispersion system, which does not produce waste gas or waste liquid, has low cost and good environmental affinity, but has weak bonding with the electrode and needs to be softened in a high temperature environment to have better bonding. Summary of the invention

[0005] The present invention provides a method for preparing a high-low temperature adhesive slurry and a lithium battery separator, and a lithium battery, which solves the problem in the related art that the aqueous adhesive material used in lithium batteries has poor adhesion to the pole piece and needs to be softened in a high temperature environment to have good adhesion.

[0006] The technical solution of the present invention is as follows: A high-low temperature bonding slurry comprises the following components in parts by mass: 10-15 parts of bonding material, 5-15 parts of thickener, 2-15 parts of binder, 0-0.5 parts of dispersant, and 50-80 parts of water. The bonding material is a low-temperature bonding material coating a high-temperature bonding material, and the raw materials of the bonding material include a low-temperature bonding material and a high-temperature bonding material in a mass ratio of 1:9-9:1.

[0007] As a further technical solution, the thickener includes one or two of sodium carboxymethyl cellulose and polyacrylamide.

[0008] As a further technical solution, the binder includes one or both of polyvinyl alcohol and acrylic acid.

[0009] As a further technical solution, the dispersant includes one or more of a quaternary ammonium salt dispersant, an acrylate polymer dispersant, and a polyester polymer dispersant.

[0010] As a further technical solution, the mass of the low-temperature adhesive material is ≤ the mass of the high-temperature adhesive material.

[0011] The present invention limits the mass of the low-temperature adhesive material to ≤ the mass of the high-temperature adhesive material, thereby further improving the high- and low-temperature bonding strength between the adhesive slurry and the pole piece.

[0012] As a further technical solution, the mass ratio of the low-temperature adhesive material to the high-temperature adhesive material is 1:2~4.

[0013] The present invention limits the mass ratio of the low-temperature adhesive material to the high-temperature adhesive material to 1:2-4, which further improves the high and low temperature bonding strength between the adhesive slurry and the pole piece.

[0014] As a further technical solution, the low-temperature adhesive material is a polyacrylate polymer, and the high-temperature adhesive material is a fluorine-containing polymer.

[0015] As a further technical solution, the polyacrylate polymer is polymethyl methacrylate, and the fluorine-containing polymer can be any polymer containing fluorine atoms, for example, it can be one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, preferably polyvinylidene fluoride-hexafluoropropylene copolymer.

[0016] As a further technical solution, the preparation method of the adhesive material comprises the following steps: after the low-temperature adhesive material and the high-temperature adhesive material are uniformly mixed, melt-extruded, and granulated to obtain the adhesive material.

[0017] As a further technical solution, the bonding material is an ethylene-vinyl alcohol copolymer modified bonding material.

[0018] After the adhesive material of the present invention is modified by the ethylene-vinyl alcohol copolymer, the high and low temperature bonding strength between the adhesive slurry and the pole piece is further improved.

[0019] As a further technical solution, the raw materials of the ethylene-vinyl alcohol copolymer modified adhesive material include ethylene-vinyl alcohol copolymer and adhesive material in a mass ratio of 1 to 5:15.

[0020] As a further technical solution, the raw materials of the ethylene-vinyl alcohol copolymer modified adhesive material include ethylene-vinyl alcohol copolymer and adhesive material in a mass ratio of 1:5.

[0021] The present invention stipulates that the raw materials of the ethylene-vinyl alcohol copolymer modified adhesive material include ethylene-vinyl alcohol copolymer and adhesive material in a mass ratio of 1:5, which further improves the high and low temperature adhesion between the adhesive slurry and the pole piece.

[0022] As a further technical solution, the preparation method of the ethylene-vinyl alcohol copolymer modified adhesive material includes the following steps: dissolving the ethylene-vinyl alcohol copolymer in a solvent, adding an adhesive material and mixing evenly, and drying to obtain the ethylene-vinyl alcohol copolymer modified adhesive material.

[0023] As a further technical solution, the solvent may be any solvent that dissolves ethylene-vinyl alcohol copolymer, preferably a mixed solvent of water and n-propanol.

[0024] The present invention also proposes a method for preparing a lithium battery separator, comprising the following steps: coating the high and low temperature adhesive slurry on the surface of a polyolefin base film, and drying to obtain a lithium battery separator.

[0025] As a further technical solution, the coating includes one of full coating, spot coating, intermittent coating and stripe coating.

[0026] As a further technical solution, the full coating is carried out by gravure coating; As a further technical solution, the point coating is made into random dots by spraying or into a matrix of uniformly distributed dots by using a point coating device.

[0027] The present invention also provides a lithium battery, the raw materials of which include the lithium battery separator.

[0028] The working principle and beneficial effects of the present invention are: The present invention provides a high-low temperature bonding slurry with good bonding strength with a pole piece, comprising a bonding material, a thickener, a binder, a dispersant and water, wherein the bonding material is a low-temperature bonding material coated with a high-temperature bonding material, and the bonding material not only has room temperature bonding properties, but also has strong high-temperature bonding properties, and its bonding temperature range covers most scenarios of lithium batteries from cell preparation to subsequent use, so that the diaphragm and the pole piece have sufficient bonding properties, and the stable performance of the cell throughout its life cycle can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0030] Figure 1This is a SEM image of a lithium battery separator with a spot coating prepared by the high and low temperature adhesive slurry obtained in Example 1 of the present invention, magnified 15.00K times; Figure 2 This is a SEM image of a lithium battery separator with a spot-coated adhesive coating prepared with the high and low temperature adhesive slurry obtained in Example 1 of the present invention, magnified 100 times; Figure 3 This is a SEM image of a lithium battery separator with a spot-coated adhesive coating prepared with the high and low temperature adhesive slurry obtained in Comparative Example 1 of the present invention, magnified 15.00K times. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The parameters of the raw materials in the following examples and comparative examples are as follows: Polymethyl methacrylate is PMMA CM-211; The brand of polyvinylidene fluoride-hexafluoropropylene copolymer is sigma, with an average Mw of 400,000 and an average Mn of 130,000; Ethylene-vinyl alcohol copolymer was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd., catalog number: 55207345; Polyvinyl alcohol is PVA 2488; The polyacrylamide is a cationic polyacrylamide with a weight average molecular weight of 18 million.

[0033] Example 1 S1, 13.5 parts of polymethyl methacrylate and 1.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain an adhesive material; S2, 69.9 parts of water and 0.1 parts of octadecyl dimethyl benzyl ammonium chloride quaternary ammonium salt were mixed and stirred for 10 minutes, 15 parts of adhesive material were added and continued to stir for 90 minutes, 5 parts of sodium carboxymethyl cellulose were added and continued to stir for 10 minutes, and finally 10 parts of polyvinyl alcohol were added and stirred for 30 minutes to obtain a high and low temperature adhesive slurry (SEM picture as shown in FIG. Figure 1 as shown).

[0034] Example 2 S1, 13.5 parts of polymethyl methacrylate and 1.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain an adhesive material; S2. Mix 50 parts of water and 0.5 parts of EFKA-4560 high molecular weight polyacrylate dispersant and stir for 5 minutes, then add 10 parts of adhesive material and continue stirring for 10 minutes, add 10 parts of polyacrylamide and continue stirring for 5 minutes, and finally add 2 parts of acrylic acid and stir for 5 minutes to obtain a high and low temperature adhesive slurry.

[0035] Example 3 S1, 13.5 parts of polymethyl methacrylate and 1.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain an adhesive material; S2. Stir 80 parts of water and 13 parts of adhesive material for 120 minutes, add 15 parts of polyacrylamide and continue stirring for 20 minutes, and finally add 15 parts of acrylic acid and stir for 30 minutes to obtain a high and low temperature adhesive slurry.

[0036] Example 4 The only difference from Example 1 is: S1, 7.5 parts of polymethyl methacrylate and 7.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain a bonding material.

[0037] Example 5 The only difference from Example 1 is: S1, 5 parts of polymethyl methacrylate and 10 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain a bonding material.

[0038] Example 6 The only difference from Example 1 is: S1, 3 parts of polymethyl methacrylate and 12 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain a bonding material.

[0039] Example 7 The only difference from Example 1 is: S1, 1.5 parts of polymethyl methacrylate and 13.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are mixed evenly, melt-extruded, and granulated to obtain a bonding material.

[0040] Example 8 S1, after 3 parts of polymethyl methacrylate and 12 parts of polyvinylidene fluoride-hexafluoropropylene copolymer are uniformly mixed, melt-extruded, and granulated to obtain a bonding material; S2, dissolving 1 g of ethylene-vinyl alcohol copolymer in 100 mL of a mixed solvent of water and n-propanol in a volume ratio of 1:1, adding 15 g of an adhesive material, stirring at 500 rpm for 20 min to mix evenly, filtering, and drying to obtain an ethylene-vinyl alcohol copolymer modified adhesive material; S3. Mix 69.9 parts of water and 0.1 parts of octadecyl dimethyl benzyl ammonium chloride quaternary ammonium salt and stir for 10 minutes, then add 15 parts of ethylene-vinyl alcohol copolymer modified adhesive material and continue stirring for 90 minutes, add 5 parts of sodium carboxymethyl cellulose and continue stirring for 10 minutes, and finally add 10 parts of polyvinyl alcohol and stir for 30 minutes to obtain a high and low temperature adhesive slurry.

[0041] Example 9 The only difference from Example 8 is: 3 g of ethylene-vinyl alcohol copolymer.

[0042] Example 10 The only difference from Example 8 is: 5 g of ethylene-vinyl alcohol copolymer.

[0043] Comparative Example 1 69.9 parts of water and 0.1 parts of octadecyl dimethyl benzyl ammonium chloride quaternary ammonium salt were mixed and stirred for 10 minutes, and then 13.5 parts of polymethyl methacrylate and 1.5 parts of polyvinylidene fluoride-hexafluoropropylene copolymer were added and stirred for 90 minutes, and then 5 parts of sodium carboxymethyl cellulose were added and stirred for 10 minutes, and finally 10 parts of polyvinyl alcohol were added and stirred for 30 minutes to obtain a high and low temperature adhesive slurry (SEM picture as shown in FIG. Figure 2 as shown).

[0044] Preparation of lithium battery separator: (1) The high and low temperature adhesive slurry obtained in Example 1 was spot coated on the surface of a polyolefin base film at a speed of 130 m / min. The thickness of the polyolefin base film was 5 μm. The surface moisture of the coating was dried in an oven at 80°C to obtain a spot-coated adhesive coating lithium battery separator. The coating thickness was 3.5 μm and the coverage was 15%. The SEM image is as follows: Figure 1~2 shown.

[0045] (2) The high and low temperature adhesive slurry obtained in Example 1 was roller coated on the surface of a polyolefin base film at a speed of 100 m / min. The thickness of the polyolefin base film was 5 μm. The surface moisture of the coating was dried in an oven at 80°C to obtain a lithium battery separator with a fully roller-coated adhesive coating. The coating thickness was 1.5 μm.

[0046] (3) The high and low temperature adhesive slurry obtained in Example 1 was sprayed on the surface of a polyolefin base film at a speed of 130 m / min. The thickness of the polyolefin base film was 5 μm. The surface moisture of the coating was dried in an oven at 80°C to obtain a sprayed adhesive coating lithium battery separator. The coating thickness was 3.5 μm and the coverage was 28%.

[0047] (4) The high and low temperature adhesive slurry obtained in Comparative Example 1 was spot coated on the surface of a polyolefin base film at a speed of 130 m / min. The thickness of the polyolefin base film was 5 μm. The surface moisture of the coating was dried in an oven at 80°C to obtain a spot-coated adhesive coating lithium battery separator. The coating thickness was 3.5 μm and the coverage was 15%. The SEM image is as follows: Figure 3 shown.

[0048] Performance Test: The high and low temperature adhesive slurries obtained in Examples 1 to 10 and Comparative Example 1 were subjected to an adhesion test. The test method was as follows: referring to the method for preparing a lithium battery separator (1), the high and low temperature adhesive slurries obtained in Examples 1 to 10 and Comparative Example 1 were respectively prepared into spot-coated adhesive coated lithium battery separators and spot-coated adhesive coated pole pieces. Then, 100 mm × 30 mm samples were cut and placed under a hot press with one side of the separator coating corresponding to the other side of the pole piece coating. The samples were hot pressed at 80° C. and 0.3 MPa for 1 s. Then, an electronic tensile tester was used to measure the adhesion between the separator coating and the pole piece coating. The results are shown in Table 1.

[0049] Table 1 Adhesion between diaphragm coating and pole piece coating

[0050] As can be seen from Table 1, the bonding slurry provided by the present invention has a bonding strength of more than 1.2 N / m at 30°C, more than 2.1 N / m at 50°C, more than 2.7 N / m at 70°C, and more than 3.3 N / m at 90°C, and has good high and low temperature bonding strength with the electrode.

[0051] Compared with Comparative Example 1, in Example 1, low-temperature adhesive material is added to coat the high-temperature adhesive material, and the bonding strength of the obtained adhesive slurry at 30°C, 50°C, 70°C and 90°C is better than that of Comparative Example 1, indicating that low-temperature adhesive material coating high-temperature adhesive material as an adhesive material can improve the high and low temperature bonding strength between the adhesive slurry and the electrode.

[0052] The bonding strength of the bonding slurries obtained in Examples 4 to 7 at 30°C, 50°C, 70°C and 90°C are better than that of Example 1, indicating that the quality of the low-temperature bonding material is ≤ the quality of the high-temperature bonding material, further improving the high and low temperature bonding strength of the bonding slurry and the electrode.

[0053] The bonding strength of the bonding slurries obtained in Examples 5-6 at 30°C, 50°C, 70°C and 90°C are better than those in Example 4 and Example 7, indicating that the mass ratio of the low-temperature bonding material to the high-temperature bonding material is 1:2-4, which further improves the high and low temperature bonding strength of the bonding slurry and the electrode.

[0054] The bonding strength of the bonding slurries obtained in Examples 8 to 10 at 30°C, 50°C, 70°C and 90°C are better than that of Example 6, indicating that the high and low temperature bonding strength of the bonding slurry and the electrode is further improved after the bonding material is modified by the ethylene-vinyl alcohol copolymer.

[0055] The bonding strength of the bonding slurry obtained in Example 9 at 30°C, 50°C, 70°C and 90°C is better than that of Example 8 and Example 10, indicating that the mass ratio of ethylene-vinyl alcohol copolymer to the bonding material is 1:5, which further improves the high and low temperature bonding strength between the bonding slurry and the electrode.

[0056] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high and low temperature bonding slurry, characterized in that: The invention comprises the following components in parts by weight: 10 to 15 parts of adhesive material, 5 to 15 parts of thickener, 2 to 15 parts of binder, 0 to 0.5 parts of dispersant and 50 to 80 parts of water. The adhesive material is a low-temperature adhesive material coating a high-temperature adhesive material. The raw materials of the adhesive material include a low-temperature adhesive material and a high-temperature adhesive material in a mass ratio of 1:9 to 9:

1.

2. The high and low temperature bonding slurry according to claim 1, characterized in that: The mass of the low-temperature adhesive material is ≤ the mass of the high-temperature adhesive material.

3. The high and low temperature bonding slurry according to claim 2, characterized in that: The mass ratio of the low-temperature adhesive material to the high-temperature adhesive material is 1:2-4.

4. The high and low temperature bonding slurry according to claim 3, characterized in that: The low-temperature adhesive material is a polyacrylate polymer, and the high-temperature adhesive material is a fluorine-containing polymer.

5. The high and low temperature bonding slurry according to claim 1, characterized in that: The preparation method of the bonding material comprises the following steps: evenly mixing the low-temperature bonding material and the high-temperature bonding material, melting and extruding, and granulating to obtain the bonding material.

6. The high and low temperature bonding slurry according to claim 5, characterized in that: The bonding material is an ethylene-vinyl alcohol copolymer modified bonding material.

7. The high and low temperature bonding slurry according to claim 6, characterized in that: The raw materials of the ethylene-vinyl alcohol copolymer modified adhesive material include ethylene-vinyl alcohol copolymer and adhesive material in a mass ratio of 1 to 5:

15.

8. The high and low temperature bonding slurry according to claim 7, characterized in that: The preparation method of the ethylene-vinyl alcohol copolymer modified adhesive material comprises the following steps: dissolving the ethylene-vinyl alcohol copolymer in a solvent, adding an adhesive material, mixing evenly, and drying to obtain the ethylene-vinyl alcohol copolymer modified adhesive material.

9. A method for preparing a lithium battery separator, characterized in that: The method comprises the following steps: coating the high and low temperature adhesive slurry described in any one of claims 1 to 8 on the surface of a polyolefin base film, and drying the slurry to obtain a lithium battery separator.

10. A lithium battery, characterized in that: The raw materials include the lithium battery separator as described in claim 9.

Citation Information

Patent Citations

  • Adhesive for lithium battery and preparation method thereof

    CN103427083A

  • Battery diaphragm and lithium ion battery and preparation method of battery diaphragm and lithium ion battery

    CN107785521A

  • High-temperature-resistant coating film, and preparation method and electrochemical device thereof

    CN113594629A

  • Lithium ion battery diaphragm with high pole piece cohesiveness and low cost and preparation method thereof

    CN115473004A

  • Hot-melt adhesive composition and bonding of polyolefin material

    JP1998102019A